(untitled) (African Journal of Biomedical Research, 2019)
For over three decades, HIV/AIDS has had a deleterious impact on public health the world over. There is still no cure for the disease although preventive strategies have evolved over the years to reduce its impact. In addition to behavioural change approaches, biomedical interventions have played a major part in reduction of HIV transmission and subsequently the burden associated with the HIV/AIDS disease. Early biomedical approaches include physical barriers such as condoms, use of clean injection equipment for intravenous drug users, blood and blood product screening. More recently, medical male circumcision and use of anti-retroviral drugs for prevention have been introduced. While these interventions have had a fundamental impact in reducing HIV incidence, the burden in many populations remains. Therefore, there is need to develop new biomedical methods to augment existing efforts. Future biomedical approaches may for instance include use of compounds that modulate the body’s immune system, such as acetylsalicylic acid, to cause resistance to HIV infection. Such approaches could be added to the HIV prevention toolkit.